Relationship between latent and radiative heating fields of tropical cloud systems using synergistic satellite observations - X. Chen; C. J. Stubenrauch; G. Mandorli (Atmospheric Chemistry and Physics)
In order to investigate the relationship between latent heating (LH) and radiative heating (Qrad), in particular the heating released by mesoscale convective systems (MCSs), we used synergistic satellite-derived data from active instruments. Given the sparse sampling of these observations, we expanded the spectral LH profiles derived from the Tropical Rain Measurement Mission (TRMM-SLH) by applying artificial neural network regressions to the Clouds from InfraRed Sounders (CIRS) data and meteorological reanalyses, following a similar approach as for the expansion of the Qrad profiles. A direct comparison with the collocated TRMM-SLH data shows excellent agreement of the average profiles, but the prediction range is underestimated, in particular between 550 and 900 hPa. Noise related to discrepancies in rain fraction between TRMM and CIRS-ML (machine learning), as well as an underestimation of extremes, can be reduced by averaging over larger areas. The zonal averages of vertically integrated LH (LP) at 01:30 and 13:30 LT align well with those from the full diurnal sampling of TRMM-SLH over the ocean. For upper-tropospheric (UT) clouds with a large amount of latent heat release, the surface temperature has a larger impact on the atmospheric cloud radiative effect (ACRE) in dry environments than in humid ones, while humidity plays a large role in cool rather than in warm environments. In all situations, the cloud height is mostly responsible for the value of ACRE. The distribution of UT clouds in the LP–ACRE plane shows a very large spread in the ACRE for small values of LP, which is gradually reduced towards larger values of LP. The mean ACRE of mature MCSs increases with LP, up to about 115 W m−2. As expected, the shapes of the LH profiles of mature MCSs show that larger, more organized MCSs have a larger contribution of stratiform rain than the smaller MCSs do. Furthermore, convective organization enhances the mean ACRE of mature MCSs on average by about 10 W m−2 over the whole LP range.